ANALISIS KEBUTUHAN RUANG TERBUKA HIJAU: PENDEKATAN KEBUTUHAN OKSIGEN: Green Open Space Analysis, Oxygen Requirement Approached in Medan Baru City - Samsuri Samsuri; Anita Zaitunah; Okber Rajagukguk (Jurnal Silva Tropika, 2021)
Medan Baru is a sub-district in the downtown area, a trade and service area. The higher population growth causes a limited area of ​​an area to provide oxygen needs. Green open space filled with trees as the city's lungs is a producer of oxygen that has not been replaced. This study aims to map green open space using Landsat 8 OLI satellite imagery and estimate the need for green open space in Medan Baru District. This research was conducted for three months (April - June 2019). The analysis carried out is the NDVI transformation (Normalized Difference Vegetation Index), CO2 absorption, and O2 requirements. The NDVI transformation analysis results show that a rather dense density class dominates Medan Baru District. The analysis of green open space as an absorber of CO2 was 7569.17 tons/year. The need for O2 is 86.458 kg/day or an area of ​​0.1708 ha, and the available amount is 65.777.06 kg O2 / day or an area of ​​129.93 Ha so that when compared to RTH to oxygen demand with the area of ​​RTH currently available, it is still sufficient.